2017
DOI: 10.3126/ejdi.v19i1-2.17701
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Lending Interest Rates of Nepalese Commercial Banks

Abstract: The aim of this study is to investigate the determinants of lending rate of Nepalese commercial banks. The analysis of data was based on a sample of 6 commercial banks observed over the period 6 years (2010 to 2015

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 10 publications
(13 reference statements)
1
23
0
Order By: Relevance
“…High interest rate spreads signal banking sector inefficiency and, when that occurs, it hampers not only financial development but also economic growth as credit to productive use is constrained due to high lending rates which are a cost to investors (Nanjunga et al, 2016). Lending interest rate to charge also matters to a commercial bank since profit banks earn-the interest income-makes a significant component of their revenues (Bhattarai, 2015;Nanjunga et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…High interest rate spreads signal banking sector inefficiency and, when that occurs, it hampers not only financial development but also economic growth as credit to productive use is constrained due to high lending rates which are a cost to investors (Nanjunga et al, 2016). Lending interest rate to charge also matters to a commercial bank since profit banks earn-the interest income-makes a significant component of their revenues (Bhattarai, 2015;Nanjunga et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In context of Nepal, we came across five main research works viz. Bhattarai 2019, Bajracharya (2018), Puri et al (2018), Timsina (2016a& 2016b and Bhattarai (2016) that have analysed the lending behaviour of commercial banks in Nepal employing quantitative approaches. Those researchers have used a range of explanatory variables to examine the lending behaviour of banks ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…There are some recent empirical works analysing the lending behaviour of commercial banks in Nepal though viz. Bhattarai (2019), Bajracharya (2018), Puri et al (2018), Timsina (2016aTimsina ( & 2016b, Bhattarai (2016), etc.but explanation of this observed anomalous behaviour in credit lending has not occupied place into their analyses. Thus, we saw a clear gap in literature in context of Nepal that motivated us to estimate the degree of elasticityof sectoral lending with lending rate (also known as price elasticity) and use the estimated price elasticity to analyse the anomalous relationship observed between them.…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have been carried out globally on the bank lending determinants, such as Olokoyo (2011) who identified the volume of deposits, investment portfolio, lending rate, cash reserve requirement ratio, and liquidity ratio as the determinants of lending behavior, Bhattarai (2016) found that bank lending is determined by investment portfolio, bank size, liquidity, and cash reserve ratio, and Timsina (2016) also found that the gross domestic product and liquidity ratio of banks have an impact on bank lending behavior in Nepal but all of them didn't show the direction of impact on banks' lending behavior. Abdul Adzis et al (2018) investigated the determinants of commercial banks' lending and demonstrated that bank size and volume of deposit positively influence commercial bank lending, while liquidity negatively influences bank lending activities.…”
Section: Literatures Reviewmentioning
confidence: 99%
“…Depending on the research hypothesis and literature reviewed, the explanatory variables used in this study to determine the commercial banks lending in Ethiopia are bank-specific factors (such as deposit, capital adequacy, profitability, bank size, and liquidity), industry-specific factors (such as average lending rate, cash reserve requirement, and bank concentration) and macroeconomic factors (such as real GDP growth rate and inflation rate). Those variables are used with different combinations and reported as significant factors that determine bank lending by various studies (Ebire & Ogunyinka, 2018;Olaoluwa and Shomade, 2017;Bhattarai, 2016;Temesgen, 2016;Malede, 2014). Table 1 presents the summary of variables and their expected effect on commercial bank lending.…”
Section: Independent Variablesmentioning
confidence: 99%